Serotonin regulation of mitochondria in kidney diseases - Kevin Hurtado; Natalie E. Scholpa; Jennifer G. Schnellmann; Rick G. Schnellmann (Elsevier, 2024)
Serotonin, while conventionally recognized as a neurotransmitter in the CNS, has recently gained attention for its role in the kidney. Specifically, serotonin is not only synthesized in the kidney, but it also regulates glomerular function, vascular resistance, and mitochondrial homeostasis. Because of serotonin's importance to mitochondrial health, this review is focused on the role of serotonin and its receptors in mitochondrial function in the context of acute kidney injury, chronic kidney disease, and diabetic kidney disease, all of which are characterized by mitochondrial dysfunction and none of which has approved pharmacological treatments. Evidence indicates that activation of certain serotonin receptors can stimulate mitochondrial biogenesis (MB) and restore mitochondrial homeostasis, resulting in improved renal function. Serotonin receptor agonists that induce MB are therefore of interest as potential therapeutic strategies for renal injury and disease. Significance statement: Mitochondrial dysfunction is associated with many human renal diseases such as acute kidney injury, chronic kidney disease, and diabetic kidney disease, which are associated with increased morbidity and mortality. Unfortunately, none of these pathologies has an FDA-approved pharmacological intervention, underscoring the urgency of identifying new therapeutics for such disorders. Studies show that induction of mitochondrial biogenesis via serotonin (5-hydroxytryptamine, 5-HT) receptors reduces kidney injury markers, restores mitochondrial and renal function after kidney injury, and decreases mortality, suggesting that targeting 5-HT receptors may be a promising therapeutic avenue for mitochondrial dysfunction in kidney diseases. While numerous reviews describe the importance of mitochondria and mitochondrial quality control mechanisms in kidney disease, the relevance of 5-HT receptor-mediated mitochondrial metabolic modulation in the kidney has yet to be thoroughly explored.